Effect of Xylan and Rice Husk on Feruloyl Esterase Activity in Penicillium Rubens - Chavez-Rosales, R; Gil-Duran, C (Biblioteca Universidad de Cordoba, 2020)
Objective. Analyzed the effect of xylan and rice husk as sole sources of carbon on the FAE activity and expression of faeA and faeB genes of Penicillium rubens (Wisconsin 54-1255), in submerged fermentation. Materials and methods. The fermentations were carried out for 24, 48, and 72 h (28°C/250 rpm), in flasks with a modified Sakamoto medium. FAE activity was determined using the synthetic substrate Ethyl 4-hydroxy-3-methoxycinnamate. The transcription of faeA and faeB was analyzed by RT-PCR. The PCR products were resolved by electrophoresis and analyzed by densitometry. Results. The analysis of gene expression showed that the use of xylan had a positive effect on the expression of both genes. The highest transcriptional activity of both faeA and faeB was detected at 48 h. On the other hand, rice husk showed negative results. The data obtained when the FAE activity was determined, supported the results observed in the gene expression analysis. Conclusion. Different from xylan the rice husk did not demonstrate an inducer effect on the feruloyl esterase activity in P. rubens. © 2021. All Rights Reserved.